ESG and Corporate Performance: The Moderating Role of TMT Functional Diversity - Cao, Huashen (International Journal of Economics and Financial Issues, 2025)
This study investigates the impact of Environmental, Social, and Governance (ESG) on corporate performance, with a focus on the moderating role of top management team (TMT) functional diversity. Utilizing a panel dataset of Chinese A-share listed companies from 2009 to 2020, we find a significant positive association between ESG performance and corporate performance, with TMT functional diversity serving as a positive moderator. Building on these findings, we recommend that firms place emphasis on TMT diversity, cross-functional collaboration, and ESG-related expertise to enhance ESG strategy implementation. The study demonstrates that leveraging the functional diversity of the TMT can help firms better formulate and implement ESG strategies, thereby improving long-term corporate performance and sustainability.